Proteína C-reativa ultrassensível e fatores de risco cardiovascular em idosos - Moreira, Andreia da Silva (2015)
Objective: To investigate the association between the elevated High-Sensitivity C-Reactive Protein (hs-CRP) and cardiovascular risk factors in elderly registered in the Family Health Strategy (FHS) of Campina Grande-PB. Material and methods: Cross-sectional study of home-based primary data collection, carried out with the elderly of both sexes. The variables analysed were: sociodemographic, anthropometric indexes, lifestyle habits, lipid fractions, glucose, blood pressure, number of chronic diseases mentioned, family history of myocardial infarction and hs-CRP. To identify associated factors, simple and multiple regression logistic analyses were performed using the SPSS 22. It was also estimated cardiovascular risk by Framingham risk score and risk reclassification performed according to the presence of elevated hs-CRP. Results: 125 elderly were evaluated (62.4% women) with a mean age of 69.71 years (SD ± 7.97). The prevalence of elevated hs-CRP was 49.6%. In the final model, a elevated hs-CRP was associated with low HDL-c (OR = 2.63; 95% CI: 1.06 to 6.52), overweight / obesity (OR = 3.07, 95% CI 1.12 to 8.45), high total cholesterol (OR = 2.65; 95% CI 1.06 to 6.67), and marital status without a partner (OR = 3.23, 95% CI 1.14 to 9.18). In the analysis of the influence of hs-CRP in the reclassification of perceived risk, 124 elderly (62.1 % female) were evaluated and cardiovascular risk was predominantly high in men (85.1 %) and women (79.2%). Of the 22 elderly classified at intermediate risk by traditional score, 9 (7,2%) who had elevated hs-CRP were reclassified as high risk. Conclusion: The low HDL- c, overweight/obesity and high total cholesterol were associated with high hs-CRP and the addition thereof to the Framingham score moderately increased the prediction of cardiovascular risk among the elderly. The measurement of hs-CRP can assist in early detection and primary and secondary prevention of cardiovascular disease.